Avaliação do sistema de drenagem e manejo das águas pluviais do município de Louveira – SP - Soares, Taynara dos Santos (Universidade Federal de São Carlos, 2025)
Accelerated and unplanned urbanization poses significant challenges for municipalities, particularly concerning solid waste management, land use, and urban drainage systems. Soil impermeabilization and irregular occupation exacerbate surface runoff, leading to flooding and hindering water infiltration, while improper waste disposal often clogs drainage systems, amplifying environmental and urban impacts. These issues are further intensified by limited financial and technical resources, complicating the implementation of sustainable solutions. This study evaluates the efficiency of the urban drainage system and stormwater management in Louveira, São Paulo, focusing on obstacles related to unregulated urbanization and infrastructure limitations. The analysis draws on the National Solid Waste Policy (Law No. 12.305/2010), the Basic Sanitation and Drainage Law (Law No. 11.445/2007), local land use laws (Municipal Law No. 2.332/2013), interview with the Environmental Management Secretariat, and an assessment of the Municipal Sanitation Plan. The study aims to diagnose current water management conditions and propose sustainable solutions aligned with municipal sanitation plans and legislation. The findings highlight inefficiencies in waste management in informal areas and difficulties improving the drainage system, emphasizing the need for integrated public policies, environmental education, and sustainable urban planning.
Drainage and stormwater management system assessment of Louveira - SP municipality
Keywords: Drenagem urbana; Políticas públicas; Saneamento; Educação ambiental; Urban drainage; Solid waste; Land use; Municipal sanitation plans; Environmental education; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO